DISTRIBUTION OF CORAL REEFS IN THE WATERS OF PANGEMPANG MUARA BADAK DISTRICT KUTAI KARTANEGARA REGENCY - Adnan, Adnan; Efendi, Muchlis; Noorsheha, Noorsheha (Jurnal Perikanan Unram, 2025)
This study aims to verify the presence and map the distribution of coral reefs in the waters of Pangempang Hamlet, Muara Badak District, Kutai Kartanegara Regency. The methods used include field surveys, remote sensing image interpretation, and GIS-based spatial analysis. Data collection was conducted at 13 locations with varying depths and distances from the shore. The research results show that four locations have been verified to contain coral reef ecosystems, with areas ranging from 0.41 to 6.26 hectares. The location with the largest coral reef area is Batu Lampe Besar (6.26 hectares), which has great potential for conservation and marine ecotourism. Acropora coral is the dominant coral species found, as it was identified at every surveyed location. Based on these findings, it is recommended to implement community-based conservation efforts, regular monitoring, and further research to ensure the sustainability of the coral reef ecosystem in the Pangempang area.